Teodise dan Teologi Kehadiran di Tengah Pergulatan Orang Tua Memahami Autisme - Nuryanto Gracia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Christian parents of children with autism often ask, “God, why is my child autistic?” This question emerges within a social context that celebrates the *cult of normalcy*, where individuals are frequently measured against socially constructed standards of normality. In their search for understanding, parents receive numerous explanations from pastors through sermons and personal counseling sessions. These responses, however, are often confined to the realm of theodicy, seeking to justify suffering and disability within the framework of divine justice and providence. Yet an important question remains: Is theodicy sufficient to address the deep existential, emotional, and spiritual struggles experienced by these parents? Through this study, the author proposes a theological framework that is more adequate for Christian parents raising children with autism. Moving beyond the limitations of theodicy, this article offers a theology of presence rooted in the mystery of the Incarnation, namely, the belief that God is present in the midst of suffering not by providing definitive answers but by accompanying humanity in its vulnerability. From a practical perspective, this article recommends that parents be supported through an honest pastoral spirituality rather than being comforted by premature theological explanations. It also calls upon the Church to cultivate genuinely inclusive communities and urges pastors to develop greater sensitivity to disability theology so that they may accompany families of children with autism as facilitators of meaning-making rather than as providers of simplistic and singular answers.